Cationized silk fibroin / oxidized sodium hyaluronate injectable hydrogel as well as preparation method and application thereof
Depending on the PEI to modify the symbolin and cross -cross the hyaluronic acid sodium hyaluronate, prepare cedicized syntomine/sodium oxide sodium hyaluronate to inject water gel, solving the existing water gel in adhesion performance, mechanical performance and antibacterial Insufficient sexuality has achieved efficient wound repair and self -healing effects.
Patent Information
- Application Number
- CN202411491942.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-24
AI Technical Summary
Existing injectable hydrogels have shortcomings in adhesion, mechanical properties and antibacterial properties, and are difficult to meet the diverse needs of the biomedical field.
Moisture symbolic protein through low molecular weight PEI to form cationic sylosumin, and uses dynamic covalenting with sodium oxide sodium hyaluronate to prepare cationic syndicate/oxide sodium oxide sodium to inject water gel.
The hydrogel has good mechanical performance, antibacterial and self -healing ability, can adapt to irregular wound repair, and shows huge application potential in the biomedical field.
Smart Images

Figure CN119371682A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomedical materials, and in particular to a cationic silk fibroin / oxidized sodium hyaluronate injectable hydrogel and a preparation method and application thereof. Background Art
[0002] Hydrogel is a three-dimensional network material composed of one or more hydrophilic polymers and is used in many fields. Among them, hydrogel, a biodegradable polymer material, has a very high hydrophilicity and biocompatibility due to its similarity to the natural extracellular matrix structure, and has physical properties and mechanical properties similar to those of living tissues. It has important application value in the fields of biomedicine and tissue engineering.
[0003] Compared with chemical covalent cross-linked hydrogels, injectable hydrogels are a new type of hydrogel cross-linked by dynamic covalent bonds or non-covalent bonds. They can be injected into the designated site and form gel in situ. After the polymer molecule solution in the sol state reaches the lesion site through the syringe, it undergoes a sol-gel transformation and forms a gel. It can yield and flow under the action of shear force, and can self-repair the damaged structure after the stress is removed. Therefore, it plays an important role in the treatment of wound healing, bone defects, cardiovascular diseases, brain diseases, etc. In addition to the characteristics of general biomaterials: non-toxic, no adverse reactions, sufficient sources, stable properties, easy storage and disinfection, good biocompatibility and tissue compatibility, etc., injectable hydrogel materials also need to have good adhesion, mechanical properties, antibacterial properties and injectability. For example, Yang Jintao et al. developed a biodegradable injectable hydrogel based on natural polysaccharides, combining the rapid Schiff base reaction between -NH2 and -CHO and the slow reaction between -NH2 and epoxy groups, which can quickly gel to fill cavities and slowly self-reinforce and support tissue repair (Biomacromolecules. 2023, 24 (7), 3345). Wu Yidong et al. used the amino groups of methacrylylated chitosan and the aldehyde and carboxyl groups on aldehyded hyaluronic acid to form reversible dynamic Schiff base bonds and electrostatic interactions, respectively, to quickly prepare a hydrogel for wound healing (Journal of Biomedical Engineering, 2021, 40 (5): 590), but it has the disadvantages of poor adhesion, low mechanical properties and no antibacterial properties. Summary of the invention
[0004] To solve the above technical problems, the purpose of the present invention is to provide a cationic silk fibroin / oxidized sodium hyaluronate injectable hydrogel and its preparation method and application, SF is modified by low molecular weight PEI, and the mechanical properties and antibacterial properties of SF are improved; cationic silk fibroin / oxidized sodium hyaluronate (CSF / OSH) hydrogel is successfully prepared by dynamic covalent crosslinking between cationic silk fibroin (CSF) and oxidized sodium hyaluronate (OSH), and the hydrogel has injectable characteristics, can adapt to irregular wound repair, and can heal spontaneously when mechanically damaged. The mechanical properties of the injectable hydrogel can be adjusted according to the mass ratio of cationic silk fibroin and sodium hyaluronate, and it has the advantages of adjustable antibacterial properties, biocompatibility, etc., and shows great application potential in the biomedical field.
[0005] The above object of the present invention is achieved through the following technical solutions:
[0006] The first aspect of the present invention provides a method for preparing a cationic silk fibroin / oxidized sodium hyaluronate injectable hydrogel, comprising the following steps:
[0007] (1) Silk fibroin (SF) is modified with polyethyleneimine (PEI) at 0-4°C to obtain cationic silk fibroin (CSF) containing an amino group (-NH2); sodium hyaluronate (SH) is oxidized to obtain oxidized sodium hyaluronate (OSH) containing an aldehyde group (-CHO);
[0008] (2) Mixing the cationic silk fibroin solution and the oxidized sodium hyaluronate solution to obtain the cationic silk fibroin / oxidized sodium hyaluronate (CSF / OSH) injectable hydrogel.
[0009] The present invention uses SF and SH as main raw materials. Both SF and SH are natural polymer materials, which can be degraded and absorbed by biological organisms, do not produce toxic and harmful substances, and have good biocompatibility. The present invention performs cation modification on SF and oxidation treatment on sodium hyaluronate. Starting from the molecular structure, the Schiff base reaction between the amino groups contained in CSF and the aldehyde groups with strong oxidizing properties contained in OSH is utilized to prepare an injectable, self-healing CSF / OSH hydrogel. The prior art usually uses a cross-linking agent to cross-link to form a hydrogel, and the cross-linking agent is usually toxic. The present invention can obtain a safe and non-toxic CSF / OSH injectable hydrogel without adding a toxic cross-linking agent.
[0010] Furthermore, in step (1), the molecular weight of the silk fibroin is 100-150 kDa.
[0011] Furthermore, in step (1), the molecular weight of the polyethyleneimine is 300-2000Da.
[0012] Furthermore, in step (1), the mass ratio of the silk fibroin to polyethyleneimine is 100:(2-10).
[0013] In a specific embodiment, the method of modifying SF with PEI is: adding PEI solution and carboxyl activation reagent to SF solution.
[0014] Furthermore, the concentration of SF in the SF solution is 5-10 mg / mL, and the concentration of PEI in the PEI solution is 0.05-2 mol / L.
[0015] Furthermore, the carboxyl activation reagent is N-hydroxysuccinimide (NHS) and 1-ethyl-3 (3-dimethylaminopropyl) carbodiimide (EDC).
[0016] Furthermore, the mass ratio of SF, NHS and EDC is 10:(1-3):(1-3).
[0017] Furthermore, in step (1), the reaction time is 5 to 7 hours.
[0018] Furthermore, in step (1), a dialysis step is also included after the reaction is completed.
[0019] Furthermore, the dialysis time is 48 to 72 hours.
[0020] Furthermore, in step (1), the sodium hyaluronate is an anionic polysaccharide with a weight average molecular weight of 100 to 120 kDa.
[0021] Furthermore, in step (1), the oxidation treatment method is: adding sodium periodate (NaIO4) to the sodium hyaluronate solution, and performing an oxidation reaction under light-proof conditions to obtain the oxidized sodium hyaluronate containing an aldehyde group.
[0022] Sodium periodate is used to oxidize sodium hyaluronate, which reduces the reaction concentration of the sodium hyaluronate solution and increases the oxidation degree of the sodium hyaluronate.
[0023] Furthermore, the concentration of sodium hyaluronate in the sodium hyaluronate solution is 2.5 to 10 mg / mL.
[0024] Furthermore, the molar ratio of sodium periodate to sodium hyaluronate in the sodium hyaluronate solution is (0.5-1.5):1, preferably (1-1.25):1.
[0025] Furthermore, a sodium periodate solution may be added to the sodium hyaluronate solution, wherein the concentration of sodium periodate in the sodium periodate solution is 0.07 to 0.1 g / mL.
[0026] Furthermore, the temperature of the oxidation treatment is room temperature.
[0027] Furthermore, the oxidation reaction time is 1 to 3 hours.
[0028] Furthermore, the method further comprises the step of adding ethylene glycol to terminate the oxidation reaction.
[0029] Furthermore, the mass ratio of ethylene glycol to sodium periodate is (1-3):1.
[0030] Furthermore, after the oxidation reaction is completed, the steps of dialysis purification and freeze drying are also included.
[0031] Furthermore, the dialysis time is 48 to 72 hours.
[0032] Furthermore, in step (2), the concentration of cationic silk fibroin in the cationic silk fibroin solution is 4-6 wt %, and the concentration of oxidized sodium hyaluronate in the oxidized sodium hyaluronate solution is 4-6 wt %.
[0033] Furthermore, in step (2), the mass ratio of the cationic silk fibroin to the oxidized sodium hyaluronate is 1:(0.5-3), preferably 1:(1-2).
[0034] Furthermore, in step (2), the mixing temperature is at room temperature and does not exceed 40°C, and can be 20-40°C.
[0035] In a specific embodiment, the cationic silk fibroin solution and the oxidized sodium hyaluronate solution are respectively placed into two tubes of a dual injector, and the cationic silk fibroin / oxidized sodium hyaluronate injectable hydrogel is obtained by injection.
[0036] The second aspect of the present invention provides a cationic silk fibroin / oxidized sodium hyaluronate injectable hydrogel obtained by the preparation method described in the first aspect.
[0037] The CSF / OSH injectable hydrogel provided by the present invention has good mechanical properties, and the mechanical properties of the hydrogel can be adjusted by changing the mass ratio of CSF to OSH.
[0038] The CSF / OSH injectable hydrogel provided by the present invention can simulate the three-dimensional network structure of the extracellular matrix to a large extent, promote cell adhesion and proliferation, and endow the hydrogel scaffold with certain antibacterial properties.
[0039] The third aspect of the present invention provides the use of the cationic silk fibroin / oxidized sodium hyaluronate injectable hydrogel described in the second aspect in tissue engineering.
[0040] The CSF / OSH injectable hydrogel provided by the present invention can be injected into irregularly shaped wound sites to form gel in situ, and heal spontaneously when damaged by external forces; at the same time, the hydrogel has good adhesion, mechanical properties, antibacterial properties and injectability, and plays an important role in the treatment of wound healing, bone defects, cardiovascular diseases, brain diseases and other treatment fields.
[0041] Beneficial effects of the present invention:
[0042] The present invention uses low molecular weight PEI to modify SF to prepare CSF containing amino groups, and changes the surface charge of SF to flip it to positive charge, which can not only increase the mechanical properties of the hydrogel three-dimensional network structure, delay the degradation rate, and promote cell proliferation, but also give the hydrogel scaffold a certain antibacterial property. The CSF / OSH injectable hydrogel provided by the present invention does not need to add any cross-linking agent, and the amino groups on CSF react with the aldehyde groups of OSH to form a hydrogel with injectable, self-healing, antibacterial and other functions through cross-linking, which has broad application prospects in the fields of biomedicine and tissue engineering. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 Schematic diagram of the dual injector and injection method in Example 1.
[0044] Figure 2 This is the infrared absorption spectrum of SF and CSF in Example 1.
[0045] Figure 3 The hydrogen nuclear magnetic resonance spectra of PEI, SF and CSF in Example 1 are shown in FIG.
[0046] Figure 4 This is the infrared absorption spectrum of SH and OSH in Example 1.
[0047] Figure 5 The hydrogen nuclear magnetic resonance spectrum of SH and OSH in Example 1 is shown in FIG.
[0048] Figure 6 The cross-sectional SEM images of the CSF / OSH injectable hydrogels prepared in Examples 1 and 6 to 8; wherein, a1, a2 and a3 are from Example 6, with scales of 100 μm, 50 μm and 20 μm, respectively; b1, b2 and b3 are from Example 7, with scales of 100 μm, 50 μm and 20 μm, respectively; c1, c2 and c3 are from Example 1, with scales of 100 μm, 50 μm and 20 μm, respectively; and d1, d2 and d3 are from Example 8, with scales of 100 μm, 50 μm and 20 μm, respectively.
[0049] Figure 7The test results of scanning the CSF / OSH injectable hydrogels prepared in Example 1 and Examples 6 to 8 using a rheometer; wherein, (a) is a G' (storage modulus) and G" (loss modulus) data graph obtained by time scanning of CSF / OSH injectable hydrogels with different mass ratios, (b) is a G' and G" data graph obtained by frequency scanning of CSF / OSH injectable hydrogels with different mass ratios, (c) is a G' and G" data graph obtained by oscillating strain scanning of the CSF / OSH injectable hydrogel of Example 6, (d) is a G' and G" data graph obtained by oscillating strain scanning of the CSF / OSH injectable hydrogel of Example 7, (e) is a G' and G" data graph obtained by oscillating strain scanning of the CSF / OSH injectable hydrogel of Example 1, and (f) is a G' and G" data graph obtained by oscillating strain scanning of the CSF / OSH injectable hydrogel of Example 8.
[0050] Figure 8 The graphs are test results of alternating strain scanning of the CSF / OSH injectable hydrogels prepared in Example 1 and Examples 6 to 8 using a rheometer, wherein (a) is Example 6, (b) is Example 7, (c) is Example 1, and (d) is Example 8.
[0051] Fig. 9 This is a self-healing test diagram of the CSF / OSH injectable hydrogel prepared in Example 1.
[0052] Fig.10 This is a shear frequency scanning data diagram of the CSF / OSH injectable hydrogel prepared in Example 1 and Examples 6 to 8.
[0053] Fig.11 These are the antibacterial experimental diagrams of the blank control group, the SF / SH hydrogel prepared in comparative example 1, and the CSF / OSH injectable hydrogel prepared in example 1 against Escherichia coli.
[0054] Fig.12 This is a graph showing the CCK-8 test results of the blank control group, the SF / SH hydrogel extract prepared in Comparative Example 1, and the CSF / OSH injectable hydrogel extract prepared in Example 1 after co-culturing with L929 cells for 1, 3, and 5 days. DETAILED DESCRIPTION
[0055] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0056] The present invention provides a method for preparing a cationic silk fibroin / oxidized sodium hyaluronate injectable hydrogel, comprising the following steps:
[0057] (1) Silk fibroin (SF) is modified with polyethyleneimine (PEI) at 0-4°C to obtain cationic silk fibroin (CSF) containing an amino group (-NH2); sodium hyaluronate (SH) is oxidized to obtain oxidized sodium hyaluronate (OSH) containing an aldehyde group (-CHO);
[0058] (2) Mixing the cationic silk fibroin solution and the oxidized sodium hyaluronate solution to obtain the cationic silk fibroin / oxidized sodium hyaluronate (CSF / OSH) injectable hydrogel.
[0059] In a specific embodiment, in step (1), the method of modifying SF with PEI is: adding PEI solution and carboxyl activation reagent to SF solution.
[0060] In a specific embodiment, the carboxyl activation reagent is N-hydroxysuccinimide (NHS) and 1-ethyl-3 (3-dimethylaminopropyl) carbodiimide (EDC).
[0061] In step (1), the reaction equation for PEI modification of SF is as follows:
[0062]
[0063] Under the action of EDC, the carboxyl groups of aspartic acid and glutamic acid in the side chain of SF are activated and react with the -N=C- double bond in EDC to generate an unstable intermediate product O-isourea derivative; then, the free hydroxyl group (-OH) on NHS reacts with the unstable intermediate product to generate a stable intermediate product, and the amino group of PEI reacts with this product to generate an aminolysis reaction. At this point, the -COOH of the side chain of SF is connected to the -HN2 of PEI by an amide bond, and the side chain of SF is modified to obtain CSF containing -NH2.
[0064] In a specific embodiment, in step (1), the oxidation treatment method is: adding sodium periodate (NaIO4) to the SH solution to carry out an oxidation reaction to obtain the OSH containing an aldehyde group.
[0065] In step (1), the reaction equation for preparing OSH from SH is as follows:
[0066]
[0067] The CC bond in the vicinal diol in the structural unit of SH can be oxidized by NaIO4 and then the ring is broken to generate an aldehyde group. NaIO4 is unstable and easily decomposes when exposed to light, so the oxidation reaction must be carried out smoothly under light-proof conditions.
[0068] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0069] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.
[0070] Example 1
[0071] A method for preparing a cationic silk fibroin / oxidized sodium hyaluronate (CSF / OSH) injectable hydrogel comprises the following steps:
[0072] (1) Take 400 mL of 5 mg / mL SF (molecular weight 100 kDa) solution and equilibrate it in an ice bath for 30 min. Then add 12 mL of 10 mg / mL PEI (molecular weight 1800 Da) solution. Then quickly add 20 mL of 10 mg / mL NHS and EDC. After reacting in an ice bath for 6 h, the solution is allowed to stand overnight and then dialyzed in deionized water for 3 days to obtain CSF solution, which is stored at 4-8°C for future use.
[0073] (2) Take 0.5 g of SH powder and dissolve it in 100 mL of deionized water. When SH is completely dissolved, weigh NaIO4 powder (the molar ratio of NaIO4 to SH is 1.25:1) and add it to the SH solution. Mix and stir for 2 h in a dark environment. Then add 1.0 mL of ethylene glycol to the solution and stir for 1 h to terminate the reaction. After the reaction is completed, put it into a dialysis bag and dialyze it in deionized water for purification for three days. After dialysis, freeze-dry it for two days to obtain a white spongy solid, which is OSH. Store it at 4-8°C for future use.
[0074] (3) OSH was dissolved in deionized water to obtain an OSH solution, and a CSF solution (concentration of 5 wt%) and an OSH solution (concentration of 5 wt%) were respectively placed in tubes A and B of a double injector, wherein the mass ratio of OSH in the OSH solution to CSF in the CSF solution was 2:1, and a CSF / OSH injectable hydrogel was obtained by injection. A schematic diagram of the double injector and its injection method is shown in FIG. Figure 1 shown.
[0075] Figure 2 is the infrared absorption spectrum of SF and CSF in Example 1, Figure 3is the nuclear magnetic resonance hydrogen of PEI, SF and CSF in Example 1 ( 1 H-NMR) spectrum. Figure 2 It can be seen that after PEI modification, SF has a peak at 1642 cm -1 、1235cm -1 and 944cm -1 The absorption peaks at 1634 cm -1 、1228cm -1 and 951cm -1 The shift indicates that the carboxyl group on the side chain of SF reacts with -NH2 of PEI to form a new amide bond. 1 In the H-NMR spectrum, a new proton peak appeared at the k point δ~3.14ppm, which corresponds to the chemical shift corresponding to the methylene proton adjacent to the amide bond in the -CONHCH2CH2NH group, indicating that the -COOH on the SF side chain reacted with the -NH2 of PEI to form an amide bond, indicating that CSF was successfully prepared.
[0076] Figure 4 is the infrared absorption (FT-IR) spectrum of SH and OSH in Example 1, Figure 5 The SH and OSH in Example 1 are H NMR spectra. The SH structure contains many hydroxyl groups, which are easy to form hydrogen bonds with electron-donating groups such as -OH and -NH2. The more hydrogen bonds there are, the broader the stretching vibration peak of -OH. Figure 4 Medium 3288cm -1 The absorption peak at 1740 cm is the stretching vibration peak of OSH and SH. -1 There is a weak absorption peak at , which is attributed to the C=O bending vibration absorption peak in the ketone or aldehyde structure, indicating that the vicinal diol structure of SH is successfully oxidized to generate two aldehyde groups. Figure 5 It can be seen that OSH has a relatively small new peak at δ~4.85-5.00ppm (points a and b) relative to SH, which corresponds to the formation of hemiacetal proton H by the aldehyde group and the adjacent hydroxyl group, while no corresponding new peak is observed in the spectrum of SH. This indicates that sodium periodate oxidizes the vicinal diol structure of SH to generate an aldehyde group, indicating that OSH was successfully prepared.
[0077] Example 2
[0078] A method for preparing a cationic silk fibroin / oxidized sodium hyaluronate (CSF / OSH) injectable hydrogel is basically the same as Example 1, except that in step (2), the molar ratio of NaIO4 to SH is 0.5:1.
[0079] Example 3
[0080] A method for preparing a cationic silk fibroin / oxidized sodium hyaluronate (CSF / OSH) injectable hydrogel is basically the same as Example 1, except that in step (2), the molar ratio of NaIO4 to SH is 0.75:1.
[0081] Example 4
[0082] A method for preparing a cationic silk fibroin / oxidized sodium hyaluronate (CSF / OSH) injectable hydrogel is basically the same as Example 1, except that in step (2), the molar ratio of NaIO4 to SH is 1:1.
[0083] Example 5
[0084] A method for preparing a cationic silk fibroin / oxidized sodium hyaluronate (CSF / OSH) injectable hydrogel is basically the same as that of Example 1, except that in step (2), the molar ratio of NaIO4 to SH is 1.5:1.
[0085] Example 6
[0086] A method for preparing a cationic silk fibroin / oxidized sodium hyaluronate (CSF / OSH) injectable hydrogel is basically the same as that in Example 1, except that in step (3), the mass ratio of OSH in the OSH solution to CSF in the CSF solution is 0.5:1.
[0087] Example 7
[0088] A method for preparing a cationic silk fibroin / oxidized sodium hyaluronate (CSF / OSH) injectable hydrogel is basically the same as that of Example 1, except that in step (3), the mass ratio of OSH in the OSH solution to CSF in the CSF solution is 1:1.
[0089] Example 8
[0090] A method for preparing a cationic silk fibroin / oxidized sodium hyaluronate (CSF / OSH) injectable hydrogel is basically the same as that of Example 1, except that in step (3), the mass ratio of OSH in the OSH solution to CSF in the CSF solution is 3:1.
[0091] Comparative Example 1
[0092] A method for preparing a silk fibroin / sodium hyaluronate (SF / SH) hydrogel comprises the following steps: mixing an SF solution (with a concentration of 5 wt%) and an SH solution (with a concentration of 5 wt%), wherein the mass ratio of SH in the SH solution to SF in the SF solution is 2:1, to obtain a SF / SH hydrogel.
[0093] The aldehyde group concentration and oxidation degree of OSH in test examples 1 to 5 were determined by potentiometric titration of hydroxylamine hydrochloride. The amino group on hydroxylamine hydrochloride easily reacts with the aldehyde group on OSH to form oxime and release HCl. The aldehyde group concentration was calculated by titrating the released HCl with NaOH. The test results are shown in Table 1:
[0094] Table 1 Data table of aldehyde concentration and oxidation degree on OSH determined by hydroxylamine hydrochloride titration method
[0095]
[0096] As can be seen from Table 1, when the molar ratio of NaIO4 to SH gradually increases from 0.5:1 to 1.5:1, the aldehyde concentration and oxidation degree on SH gradually increase. When the molar ratio increases from 1.25:1 to 1.5:1, the oxidation degree no longer increases and remains at around 47%. This may be because when the oxidation degree reaches 47%, the aldehyde concentration on OSH is very high, and it is very easy to form a hemiacetal structure with the adjacent hydroxyl group, thereby preventing the hydroxyl group on SH from further reacting with NaIO4, so the oxidation degree cannot be further increased. When the molar ratio of NaIO4 to SH is 1.25:1, the prepared OSH contains more aldehyde groups, which is conducive to the preparation of injectable hydrogels.
[0097] The cross-sections of the CSF / OSH injectable hydrogels prepared in Examples 1 and 6 to 8 were characterized using a scanning electron microscope (SEM). Figure 6 As shown in the figure, the internal structure of CSF / OSH injectable hydrogels is porous. The internal pore sizes of CSF / OSH injectable hydrogels with a mass ratio of OSH to CSF of 0.5:1, 1:1, 2:1, and 3:1 are 155.8±9.8μm, 185.1±22.3μm, 208.0±13.8μm, and 224.8±15.9μm, respectively, and the internal porosities are 46.6±2.5%, 47.6±11%, 55.4±8.6%, and 56.6±11.4%, respectively. With the increase of OSH proportion, the pore size and porosity of CSF / OSH injectable hydrogels increase, which may be because the change of OSH proportion actually changes the cross-linking density of CSF and aldehyded sodium hyaluronate, resulting in changes in the internal pore size of the gel. The pore shapes of CSF / OSH injectable hydrogels with a mass ratio of OSH to CSF of 2:1 were mostly elliptical or irregular polygonal, with uniform pores and relatively smooth pore walls.
[0098] The CSF / OSH injectable hydrogels prepared in Example 1 and Examples 6 to 8 were scanned in terms of time, frequency and oscillation strain using a rheometer. Figure 7The test result graphs are obtained by scanning the CSF / OSH injectable hydrogels prepared in Example 1 and Examples 6 to 8 using a rheometer, wherein (a) is a graph showing G' (storage modulus) and G" (loss modulus) data obtained by time scanning of CSF / OSH injectable hydrogels of different mass ratios, (b) is a graph showing G' and G" data obtained by frequency scanning of CSF / OSH injectable hydrogels of different mass ratios, (c) is a graph showing G' and G" data obtained by oscillating strain scanning of the CSF / OSH injectable hydrogel of Example 6, (d) is a graph showing G' and G" data obtained by oscillating strain scanning of the CSF / OSH injectable hydrogel of Example 7, (e) is a graph showing G' and G" data obtained by oscillating strain scanning of the CSF / OSH injectable hydrogel of Example 1, and (f) is a graph showing G' and G" data obtained by oscillating strain scanning of the CSF / OSH injectable hydrogel of Example 8. Figure 7 As can be seen in (a), the four groups of hydrogels all exhibited obvious solid characteristics (G'>G"); the G' of the CSF / OSH injectable hydrogels with a mass ratio of OSH to CSF of 0.5:1, 1:1, 2:1, and 3:1 were 72Pa, 194Pa, 350Pa, and 301Pa, respectively, under an oscillatory strain of 1%, indicating that the CSF / OSH injectable hydrogel with a mass ratio of OSH to CSF of 2:1 had the best cross-linked network. With the increase of OSH content, the G' and G" of the gel also showed an increasing trend. When the mass ratio of OSH to CSF was 2:1, the G' value of the hydrogel reached the maximum (350Pa), indicating that at this time the aldehyde group inside the hydrogel was equivalent to the amino group, the most imine bonds were formed, and it had the most stable three-dimensional network structure.
[0099] The four groups of hydrogels were tested at different frequencies with a fixed oscillating strain (1%). The G' of the four groups of hydrogels remained almost stable in the frequency range of 0.1 to 100 rad / s, and in all cases, G' was much higher than G", such as Figure 7 Moreover, when the mass ratio of OSH to CSF was 2:1, the gel had the highest G', indicating that this group of gels had the best cross-linking network, which was consistent with the gel time results.
[0100] from Figure 7It can be seen from (c) to (f) that the G' and G" of the OSH / CSF injectable hydrogel remain almost stable within the oscillation strain range of 0.1% to 50%. As the oscillation strain gradually increases, the G' of the hydrogel decreases, and the curves of G' and G" intersect, indicating the collapse of the internal network structure of the hydrogel, indicating that the hydrogel transforms from a solid with gel properties to a liquid-like with fluid properties. When the mass ratio of OSH to CSF is 2:1, the critical strain of the gel is the largest (345%), and when the mass ratio is 3:1, the critical strain is the smallest (65%). This shows that when the mass ratio of OSH to CSF is 2:1, the hydrogel has the most imine bonds and the most tightly cross-linked, so its critical strain is the largest. The larger the critical strain, the greater the deformation that the hydrogel can withstand to resist shear stress. OSH has a higher critical strain when the mass ratio of OSH to CSF is 2:1, which indicates that it can withstand greater deformation.
[0101] The CSF / OSH injectable hydrogels prepared in Example 1 and Examples 6 to 8 were subjected to alternating strain scanning using a rheometer. Figure 8 The graphs are test results of alternating strain scanning of the CSF / OSH injectable hydrogels prepared in Example 1 and Examples 6 to 8 using a rheometer, wherein (a) is Example 6, (b) is Example 7, (c) is Example 1, and (d) is Example 8. Figure 8 It can be seen that when the strain increases from 1% to 1000%, G">G', and the internal structure of the gel gradually collapses; when the strain recovers from 1000% to 1%, G'>G", and both G' and G" return to their original values, indicating that the OSH / CSF hydrogel has rebuilt its own structure and achieved self-healing.
[0102] Fig. 9 The self-healing test diagram of the CSF / OSH injectable hydrogel prepared in Example 1. The OSH / CSF injectable hydrogel was cut into two halves, one of which was dyed with methyl orange. The different colored hemihydrogels were made into small pieces and spliced together, and then placed at room temperature for observation without any other intervention. Fig. 9 It can be seen that the two hydrogels were cut into small pieces and merged into a whole. After they were put closely together, their surfaces became smooth. The two dye molecules clearly interpenetrated at the weld, indicating that the polymer molecular chains moved between adjacent hydrogel fragments. At this time, a pulling force was applied to the hydrogel with tweezers, and it was found that the hydrogel welds were still tightly connected together without any breakage. This may be because when cracks occur, the imine bonds break and free aldehyde and amide groups are exposed at the interface; the exposed amino and aldehyde groups can reconstruct new imine bonds due to their dynamic and reversible properties, allowing the hydrogel to recover from the cracks, which further illustrates that the CSF / OSH injectable hydrogel has excellent self-healing ability.
[0103] Fig.10 The shear frequency scanning data of the CSF / OSH injectable hydrogel prepared in Example 1 and Examples 6 to 8 show that the composite viscosity of the OSH / CSF hydrogel decreases with increasing shear frequency, indicating that the OSH / CSF hydrogel has pseudoplasticity, is easy to be injected by a syringe, and has excellent injectability.
[0104] Fig.11 These are the antibacterial experimental figures of the blank control group (CON), the SF / SH hydrogel prepared in comparative example 1, and the CSF / OSH injectable hydrogel prepared in example 1 against Escherichia coli. The SF / SH hydrogel has a certain antibacterial effect, and with the addition of cationic silk protein, the antibacterial rate of the CSF / OSH injectable hydrogel increases, proving that the CSF / OSH injectable hydrogel has excellent antibacterial properties against Escherichia coli.
[0105] Fig.12 The graph shows the CCK-8 test results of the blank control group (Control), the SF / SH hydrogel extract prepared in Comparative Example 1, and the CSF / OSH injectable hydrogel extract prepared in Example 1 after co-culture with L929 cells (mouse fibroblasts) for 1, 3, and 5 days. The extracts were prepared in accordance with the national standard GB / T16886.5-2017 / ISO10993-12. After 1 day of culture, the OD value of CSF / OSH injectable hydrogel was significantly higher than that of the blank control group (without hydrogel) and SF / SH hydrogel; after 3 days of culture, the OD values of each group increased significantly, among which the OD value of CSF / OSH injectable hydrogel was significantly different from that of the blank control group and SF / SH hydrogel; after 5 days of culture, the OD values of each group increased further, the OD value of the blank control group was significantly different from that of SF / SH hydrogel, and the OD value of CSF / OSH injectable hydrogel was significantly different from that of SF / SH hydrogel, which proved that CSF / OSH injectable hydrogel had no obvious toxic side effects on L929 cells and could promote the proliferation of L929 cells.
[0106] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a cationic silk fibroin / oxidized sodium hyaluronate injectable hydrogel, characterized in that: The following steps are involved: (1) Modifying silk fibroin with polyethyleneimine at 0-4° C. to obtain cationic silk fibroin containing amino groups; oxidizing sodium hyaluronate to obtain oxidized sodium hyaluronate containing aldehyde groups; (2) Mixing the cationic silk fibroin solution and the oxidized sodium hyaluronate solution to obtain the cationic silk fibroin / oxidized sodium hyaluronate injectable hydrogel.
2. The preparation method according to claim 1, characterized in that: In step (1), the molecular weight of the silk fibroin is 100-150 kDa.
3. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the silk fibroin to polyethyleneimine is 100:(2-10).
4. The preparation method according to claim 1, characterized in that: In step (1), the oxidation treatment method is: adding sodium periodate to the sodium hyaluronate solution, and performing an oxidation reaction under light-proof conditions to obtain the oxidized sodium hyaluronate containing an aldehyde group.
5. The preparation method according to claim 4, characterized in that: The concentration of sodium hyaluronate in the sodium hyaluronate solution is 2-3 mg / mL.
6. The preparation method according to claim 4, characterized in that: The molar ratio of sodium periodate to sodium hyaluronate in the sodium hyaluronate solution is (0.5-1.5):
1.
7. The preparation method according to claim 1, characterized in that: In step (2), the concentration of cationic silk fibroin in the cationic silk fibroin solution is 4-6 wt %, and the concentration of oxidized sodium hyaluronate in the oxidized sodium hyaluronate solution is 4-6 wt %.
8. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of the cationic silk fibroin to the oxidized sodium hyaluronate is 1:(0.5-3).
9. The cationic silk fibroin / oxidized sodium hyaluronate injectable hydrogel obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the cationic silk fibroin / oxidized sodium hyaluronate injectable hydrogel according to claim 9 in tissue engineering.
Citation Information
Patent Citations
Silk fibroin-based self-healing hydrogel and preparation method thereof
CN107854729A
Preparation method of carbon nanotube-temperature-sensitive gel double-slow-release type drug carrier
CN110934818A
Injectable hydrogel material and preparation method therefor and use thereof
WO2021007899A1
Cited By
Self-assembled microgel, microgel stent and preparation method and preparation device of self-assembled microgel and microgel stent
CN120554666A
Self-assembling microgels, microgel scaffolds, and methods and devices for their preparation
CN120554666B